EFFECTIVENESS OF TASK-BASED LANGUAGE TEACHING (TBLT) FOR SECONDARY SCHOOL LEARNERS - Namozova Sevinch Otabek qizi; Hasanova Sevinch Hotam qizi (TADQIQOTLAR, 2026)
Abstract In recent years, the field of English Language Teaching (ELT) has undergone notable  transformation  due  to  progress  in  pedagogical  theories,  digital  tools,  and classroom  practices.  As  a  result,  teachers  today  have  access  to  a  diverse  range  of methods  designed  to  improve  learners’  language  proficiency.  Among  these approaches, Task-Based Language Teaching (TBLT) stands out as one of the most practical  and  learner-centered  methodologies.  This  article  provides  an  in-depth overview of the advantages TBLT offers, particularly in enhancing students’ real-life communication skills and active language use. It also discusses practical strategies and considerations for educators who wish to integrate TBLT into their lessons, ensuring more effective and engaging English language learning experiences.